REGULAÇÃO TECNOIDEALISTA EDUCACIONAL NA EUROPA: O CASO ITALIANO* - Freitas, Rogério Gonçalves; Costa, Áurea De Carvalho [UNESP] (Centro de Estudos Educação e Sociedade - Cedes, 2019)
This article discusses the global phenomenon of techno-idealistic regulation in education. Our initial hypothesis is that to create a model of educational integration, European politics developed new regulatory practices from the neoliberal governance system. We aim to analyze this system in the context of the last educational reforms in Italy. It is a documentary research under the framework of historical and dialectical materialism. We conclude that the forms of disciplinary regulation of the Italian educational system to safeguard European companies in crisis, which tried to collaborate to construct new chains of value creation, through the technological innovation and the generation of a new form of alienation, i.e., a techno-idealist.

El tema de este artículo es un fenómeno global de la regulación tecno-idealista de la educación. Se parte de la hipótesis que, para crear el modelo de integración educativa, la política europea desarrolló el nuevo plan de acciones del sistema de gobernanza neoliberal. Es una investigación documental bajo la referencia del materialismo histórico y dialéctico. Se concluye que las formas de regulación disciplinaron el sistema educativo italiano para salvaguardar empresas en crisis, las cuales intentaron colaborar en la construcción de nuevas cadenas de creación de valores, por a través de la innovación tecnológica y la generación de una nueva forma de alineación, es decir, un tecno-idealista.

O tema do artigo é o fenômeno global da regulação tecnoidealista na educação. Partimos da hipótese de que, para criar o modelo de integração educacional, a política europeia desenvolveu práticas de regulação oriundas do sistema de governança neoliberal. Objetivamos analisar esse sistema no âmbito das últimas reformas educacionais na Itália. Trata-se de uma pesquisa documental sob o referencial do materialismo histórico e dialético. Concluímos que as formas de regulação disciplinaram o sistema educacional italiano para salvaguardar empresas europeias em crise, as quais tentaram colaborar para a construção de novas cadeias de criação de valor por meio da valência tecnológica e do discurso da inovação, produzindo uma nova maneira de alienação, ou seja, a tecnoidealista.
Techno-idealistic educational regulation in Europe: the Italian case
Regulación de la educación Tecno-idealista en Europa: el caso italiano
Keywords: Techno-idealistic regulation; European Neoliberalism; Educational reform; Italian education; Regulação tecnoidealista; Neoliberalismo europeu; Reforma educacional; Educação italiana